2005
DOI: 10.1242/jcs.02508
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the strength of cadherin adhesion: evidence for a novel adhesion complex

Abstract: Adherens junctions and desmosomes are critical for embryogenesis and the integrity of adult tissues. To form these junctions, classical cadherins interact via α- and β-catenin with the actin cytoskeleton, whereas desmosomal cadherins interact with the intermediate filament system. Here, we used a hormone-activated mutant N-cadherin expressed in fibroblasts to show the existence of a novel classical cadherin adhesion system. N-cadherin was fused at its C-terminus to a modified estrogen receptor ligand-binding d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 42 publications
2
17
0
1
Order By: Relevance
“…Furthermore, we have shown for the first time that, in contrast to desminopathies and Alexander disease, vimentin-containing aggregates are not terminal but transient structures that ultimately become degraded, even in postmitotic cells (Omary et al, 2004;Li et al, 2002). This activity is in line with findings on the dynamic behaviour of disease-type keratin aggregates in cultured cells but in contrast to certain polyglutamine inclusions (Werner et al, 2004;Kim et al, 2005).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, we have shown for the first time that, in contrast to desminopathies and Alexander disease, vimentin-containing aggregates are not terminal but transient structures that ultimately become degraded, even in postmitotic cells (Omary et al, 2004;Li et al, 2002). This activity is in line with findings on the dynamic behaviour of disease-type keratin aggregates in cultured cells but in contrast to certain polyglutamine inclusions (Werner et al, 2004;Kim et al, 2005).…”
Section: Discussionsupporting
confidence: 87%
“…In contrast to the keratin-desmosome linkage which has been extensively studied and is well defined by disease mutations, very little is known about how vimentin or any of the other IF proteins are attached to adhesion complexes in the lens (Fuchs and Cleveland, 1998;Getsios et al, 2004). In fibroblasts, p120 ctn has been suggested to link vimentin to N-cadherin, whereas in endothelial cells plakoglobin and desmoplakin connect vimentin to VEcadherin (Kim et al, 2005;Kowalczyk et al, 1998;Lampugnani and Dejana, 1997). Given that mutations in desmosomal proteins In control sections, both proteins were distributed underneath the plasma membrane.…”
Section: Journal Of Cell Science 121 (22)mentioning
confidence: 99%
“…By analysing several markers for EMT, we observed that EOC cells induce an EMT phenotype during spheroid formation, defined by a substantial decrease in the gene expression of the cell-cell adhesion molecule E-cadherin. This implies that EOC spheroid compaction likely depends on additional molecules or processes, such as fibronectin, vimentin or actomyosin-mediated contractility as seen in other spheroid systems [2,[37][38][39]. Since endogenous BMP signalling is reduced during spheroid formation, we propose that induction of the EMT phenotype in EOC spheroid cells does not require activation of BMP signalling.…”
Section: Discussionmentioning
confidence: 84%
“…During the initial stages of spheroid formation, cell-cell adhesion is primarily mediated by the actions of integrins and cadherins [20,36,37]. By analysing several markers for EMT, we observed that EOC cells induce an EMT phenotype during spheroid formation, defined by a substantial decrease in the gene expression of the cell-cell adhesion molecule E-cadherin.…”
Section: Discussionmentioning
confidence: 86%
“…Kin suggested that members of the cadherin family play an important role in the formation of MCS suspensions13. Shane demonstrated that tight junctions among HT29 colon tumor cells in MCS suspensions desensitized the cells to cytotoxic drugs and that disruption of E-cadherin–mediated cell-cell adhesion could restore the sensitivity to chemotherapeutics14.…”
mentioning
confidence: 99%